Warehouse model: report no. 2 - Kay, E. (College of Aeronautics, 1966)
1.1. Report No. 1 dealt with the simple warehouse model in a static sense. This was sufficient, the only consideration being optimisation of handling, i.e. the problem posed was spatial. The problem becomes a dynamic one as soon as stock policies are taken into consideration, that is, as soon as the time dimension enters the problem. 1.2. Section 3 of this report deals with the most usual of stock policies, FIFO. Section 4 discusses the rarer policies of MINDIS, - a phrase coined by the author to describe the policy of minimising movement in the warehouse regardless of age of stock, - and LIFO. Section 5 details the mathematics used.